Alaska Native Children Do Not Prefer Sugar-Sweetened Fruit Drinks Compared to Sugar-Free Fruit Drinks - Chi, Donald L. (J Acad Nutr Diet, 2019)
BACKGROUND. Alaska Native children, including children of Yup’ik descent, consume large volumes of sugar-sweetened fruit drinks, which contain added sugars that contribute to obesity, diabetes, and dental caries. To date, taste preference evaluations have not been conducted of commercially available sugar-free fruit drinks. OBJECTIVE. The study tested the hypothesis that children would have equal preference for sugar-free versus sugar-sweetened fruit drinks. DESIGN. This was an experimental two-alternative forced-choice paired preference test. PARTICIPANTS/SETTING. The study focused on a convenience sample of Yup’ik children ages 7 to 10 years recruited and enrolled from the Yukon-Kuskokwim Health Corporation dental clinic in Bethel, Alaska (N=89). INTERVENTION. Children evaluated four different commercially-available sugar-free fruit drinks paired with the sugar-sweetened versions of each flavor. Flavor pair presentation order was alternated across children and order of presentation within each of the four pairs was randomized across pairs. MAIN OUTCOME MEASURES. The outcome was taste preference for the sugar-free versus sugar-sweetened version of the fruit drink. STATISTICAL ANALYSES PERFORMED. A test of equivalence was run across all four flavors and separately for each flavor using two one-sided tests. RESULTS. The data failed to demonstrate equivalence of the sugar-free versus sugar-sweetened fruit drinks across all four flavors (P=0.51) or separately for each flavor. However, this was not because of a preference for sugar-sweetened drinks. The preference for sugar-free drinks overall and for each flavor was >50%. While the lower bounds on the 90% confidence intervals were within the range of equivalence (40% to 60%), the upper bounds were outside the range of equivalence (>60%). Based on post-hoc analyses, similar preferences were observed for Yup’ik and non-Yup’ik children, boys and girls, and by child’s age. CONCLUSIONS. Taste preference findings suggest sugar-free fruit drinks may be a well-tolerated alternative to sugar-sweetened fruit drinks for Yup’ik children in Alaska Native communities.